One-step preparation of nanosized Ag-PdCo-powder and its alloy formation at low temperature - Khanna, P. K.; Singh, N.; Kulkarni, D.; Marimuthu, R.; Charan, Shobhit; Patil, K. R.; Jain, G. H. (Synthesis and Reactivity in Inorganic Metal-Organic and Nano-Metal Chemistry, 2007)
Nano-sized silver-palladium co-powder has been synthesized from silver nitrate-palladium chloride by wet chemical method. The present experimental conditions are applied for the first time for Ag-Pd co-powders wherein sodium formaldehyde sulfoxylate (SFS) has been used as an external reducing agent to simultaneously reduce respective metal salts. SFS reduces the metal salts at room temperature thus prevents formation of bigger particles of the respective metals in co-powder. Powder X-ray diffraction measurements ( XRD) and Transmission electron microscopy ( TEM) suggest the formation of nano-sized Ag-Pd co-powder with particle diameter in the range of about 25 nm. SEM shows that the powder morphology changes with temperature. Heat treatment of 90: 10 (Ag:Pd) composition showed shift in XRD peaks indicating alloy formation of Ag/Pd at lower temperature. Thick-films generated by use of the co-powder resulted in Ag/Pd alloy at about 500 degrees C as confirmed by the XRD. Thermal analysis showed that Ag/Pd co-powders initially gain the weight due to oxidation followed by the weight loss.
Keywords: alloy; Chemical synthesis; nano-powder; noble metal; Transition Metal

One-pot synthesis of oleic acid-capped cadmium chalcogenides (CdE: E = Se, Te) nano-crystals - Khanna, P. K.; Rao, K. Srinivasa; Patil, K. R.; Singh, V. N.; Mehta, B. R. (Journal of Nanoparticle Research, 2010)
Surface-capped CdSe and CdTe nano-crystals (NCs) have been synthesized using cadmium acetate, oleic acid and respective tri-octylphosphine chalcogenide (TOPE; E = Se/Te) in diphenyl ether (DPE). Well-dispersed CdSe particles showed two absorption bands at the region of 431-34 and 458-60 nm in optical absorption study. A band-edge emission resulted at 515 nm with an excitation energy of 400 nm, in its photoluminescence (PL) spectrum. Similarly, UV-visible absorption study of CdTe revealed an absorption band at < 700 nm. The broadened X-ray diffraction (XRD) pattern showed that at higher reaction temperature cubic CdSe but hexagonal CdTe can be obtained with crystallite size of < 10 nm. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed that agglomerated particles are of spherical nature. The inter-planar spacing in CdTe was measured to be 0.406 nm, a characteristic of (100) lattice plane in hexagonal CdTe. X-ray photoelectron spectroscopy (XPS) showed that CdSe NCs have better air stability stable than CdTe. Presence of organic moiety around the semiconductor particles was confirmed by infrared (IR) spectroscopy.
Keywords: Chemical synthesis; photoluminescence; Semiconductors; Surface capping